Pattern of alcohol use and drinking antecedents in alcohol dependent patients with and without co-morbid depression: a comparative study - Mani, Anu Mary; Srinivasan, K.; Sreedaran, Priya (International Journal of Research in Medical Sciences, 2020)
Background: Few studies have compared the pattern of alcohol use in Alcohol dependence syndrome (ADS) patients with and without co-morbid depression. Assessing the pattern may throw light into prevention of relapses more effectively in alcohol dependent patients with co-morbid depression. This study was undertaken to assess the difference in pattern of drinking of alcohol in patients with alcohol dependence with and without co-morbid depression. Methods: A descriptive comparative study was designed to compare the difference in pattern of alcohol use in alcohol dependent patients with co-morbid depression and without co-morbid depression. Severity of dependence on alcohol was assessed using Alcohol Use Disorders Identification Test (AUDIT). Drinking pattern was assessed using Timeline Follow back Calender and Drinking Pattern Questionnaire. The data were statistically analysed. Results: Total 96 alcohol dependent patients (24 had co-morbid depression and 72 without co-morbid depression) were included in the study. There were no significant differences in alcohol use in both the groups in terms of AUDIT scores, amount of drinking, abstinence days or binge drinking. More frequent drinking was observed in circumstances related to emotional, physiological, financial and children related situations in patients with co-morbid depression (p<0.05). Conclusions: Drinking circumstances like emotional, physiological, financial and children related situations require more attention while assessing, treating and aiming at relapse of prevention in ADS patients with co-morbid depression.